Communicating with illiterate consumers - P. J. Du Plessis; Truida Prekel (South African Journal of Business Management, 1986)
Communicating effectively with consumers is a major problem facing marketers world-wide. In South Africa a substantial proportion of adult consumers are illiterate. Considerable potential could be unlocked if marketers were to differentiate or expand their communication strategy to specifically address illiterate consumers. It is estimated that between 40% and 50% of adult blacks in South Africa are illiterate. Exploratory research was undertaken to establish how a sample of illiterate and semi-literate blacks perceived, recognized and understood a selection of printed advertisements of consumer products. Results indicate that respondents have a high recognition of product application, and a fairly high recognition of brand names. In some cases message distortion and misinterpretation occurred, indicating that advertisers must ensure that communication with this market segment is clear, possibly by portraying a functional or product application setting. Certain brand names have become 'elevated' to generic names, an respondents tend to have fairly strong brand preferences for certain grocery products. Female respondents appear to be an important target group for advertisers of domestic consumables and grocery items because many of them influence product choice both in their own, and in their employers' homes. Marketers should establish to what extent illiterates constitute an important market segment for them, and devise specific ways to communicate with this large group of 'unnoticed' consumers.
Keywords: 650